Pendidikan dan Pekerjaan Ibu dengan Pertumbuhan dan Perkembangan anak usia dini - Dwi Ertiana (Prosiding SPIKesNas : Seminar Publikasi Ilmiah Kesehatan Nasional, 2024)
It is very important to pay attention to the process of children's growth and development from an early age, this process plays an important role in individual development. Efforts to monitor children's health as early as possible are carried out from the time the child is still in the womb until he is 5 years old, to ensure that the child can live a good life while improving the quality of life to achieve optimal growth and development. The aim is to analyze the relationship between maternal education and employment with the growth and development of early childhood in Tapos Bugenvil, Indrodelik Village, Bungah District, Gresik Regency. The type of research is analytical research. Independent variables are education and, the mother's occupation, dependent variables are growth and early childhood development. The research was carried out in Tapos Bugenvil, Indrodelik Village, Bungah District, Gresik Regency from 20 May to 22 June 2023. The research population was 85 respondents. A simple random sampling technique obtained 70 respondents. Data collection uses questionnaires, KPSP, and SDIDTK, after the data is collected, coding, scoring, tabulating, and data analysis are carried out. The results of the analysis of work and child growth (nutritional status) obtained ρ value = 0.084 > α 0.05, meaning there is no relationship between work and child growth, while the results of research analysis on the relationship between education and child growth (nutritional status) obtained ρ value = 0.046 < α 0.05 means there is a relationship between education and child growth, with a value of r= 0.393 which is in the low relationship category with a positive relationship direction. Through SDIDTK activities (stimulation of detection and early intervention of growth and development) growth and development disorders can be prevented early before children experience malnutrition. SDIDTK can prevent the possibility of mental/emotional deviations.